2004
DOI: 10.1016/j.ehj.2004.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Combined endurance/resistance training reduces NT-proBNP levels in patients with chronic heart failure

Abstract: Four months of combined endurance/resistance training significantly reduced circulating levels of NT-proBNP in patients with CHF, without evidence of adverse remodelling. Exercise training might offer additional non-pharmacological modulation of the activated neurohormonal pathways in the setting of CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 36 publications
7
83
0
1
Order By: Relevance
“…Moderate-intensity endurance exercise training has been shown to improve left ventricular function in individuals with non-BTHS heart failure as well as improve levels of plasma markers known to be associated with the severity of cardiac impairment (e.g., TNF-a and pro-BNP) (Adamopoulos et al 2002;Conraads et al 2004;Chen et al 2012). However, in the current study we did not observe improvements in resting nor exercise-stimulated left ventricular function, plasma pro-BNP, or plasma TNF-a following endurance exercise training in four participants with BTHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate-intensity endurance exercise training has been shown to improve left ventricular function in individuals with non-BTHS heart failure as well as improve levels of plasma markers known to be associated with the severity of cardiac impairment (e.g., TNF-a and pro-BNP) (Adamopoulos et al 2002;Conraads et al 2004;Chen et al 2012). However, in the current study we did not observe improvements in resting nor exercise-stimulated left ventricular function, plasma pro-BNP, or plasma TNF-a following endurance exercise training in four participants with BTHS.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because peak oxygen consumption (i.e., exercise tolerance) is the single best predictor of cardiovascular and all-cause mortality in individuals with cardiovascular disease (Myers et al 2002). In individuals with non-BTHS heart failure, endurance (aerobic) exercise training increases peak whole-body oxygen consumption, left ventricular function, skeletal muscle blood flow and oxidative function, plasma lactate concentration during exercise, and improves serum markers associated with the severity of the cardiac impairment (e.g., tumor-necrosis factor-a (TNF-a) and probrain natriuretic peptide(pro-BNP)) (Sullivan et al 1988;Minotti et al 1990;Coats et al 1992;Hambrecht et al 1997Hambrecht et al , 1998Adamopoulos et al 2002;Delagardelle et al 2002;Giannuzzi et al 2003;Conraads et al 2004;Bartlo 2007). Most importantly, endurance exercise training in patients with non-BTHS heart failure was safe, improved survival (Belardinelli et al 1999), decreased hospitalization (Belardinelli et al 1999), and increased quality of life (Coats et al 1992;Tyni-Lenne et al 1996;Belardinelli et al 1999).…”
mentioning
confidence: 99%
“…The pleiotropic stimulus of ET leaves room for mechanistic considerations regarding the beneficial effect of ET in HFpEF, including anti‐inflammation10 and reduced neuro‐hormonal activation 11. Hormonal alterations may play a pivotal role in mediating this process.…”
Section: Introductionmentioning
confidence: 99%
“…Rodrigues et al [21], Park et al [18] reported no significantly change in the end diastolic diameter and end systolic diameter after aerobic exercise. Conraads et al [2] showed a decrease in left ventricular end-systolic diameter in the trained heart failure group. Aerobic activities bring about a volume overload which increases the initial diastolic filling at rest and exercise.…”
Section: Discussionmentioning
confidence: 99%